PROGNOSIS OF DIABETIC KIDNEY DISEASE USING PROTEOMIC ANALYSIS OF URINE PROTEIN BIOMARKERS - Оmonov Аkmal Abdisalimovich; Mo‘ydinov Otabek Xusanovich; Pardabayeva S. Z.; Uzoqboyeva R. Q.; Sayfullayeva O. B.; Soataliyeva R. Sh. (Modern American Journals, 2026)
Diabetic kidney disease (DBC) is a common microvascular complication that occurs in 20–40% of patients with type 2 diabetes, leading to high morbidity and mortality rates. The diagnosis of DBK is based on stable proteinuria, an elevated albumin-to-creatinine ratio in the urine of more than 30 mg/g, a decrease in the calculated glomerular filtration rate (GFR), and a slowdown of renal function. These are biomarkers that assess the functional state of the kidneys, make it possible to identify the disease at an early stage and monitor its progress, and also makes it possible to determine the relevance of this issue in clinical practice.
Keywords: Zinc-alpha-2-glycoprotein (SAG) in blood plasma, diabetic nephropathy, albumin, SAG in urine, mg/g creatinine, GFR.